Women in twentieth century South African politics : the Federation of South African Women, its roots, growth and decline - Walker, Colin John (Department of Historical Studies, 2016)
In the history of opposition to white supremacist rule in South Africa, the 1950's stand out as a period of intensive legal resistance by black political bodies on an unprecedented mass scale. Undoubtedly, for all its weaknesses and difficulties, the Congress Alliance, with the African National Congress its senior partner, was the major source of opposition faced by the apartheid state in this period. More than is generally realised, however, the 1950's were also a decade of mass political action by black women in South Africa, that section of the population which a 1956 pamphlet aptly described as "the most oppressed, suffering and downtrodden of our people". At the centre of this outburst lay the Federation of South African Women (FSAW), an organisation that was linked to the Congress Alliance. It is the history of this organisation that forms the subject matter of this thesis. Little historical work has been done on women in South Africa, politically or otherwise: for this reason, the scope of this study is broad and, in addition to material on the history and make-up of the FSAW itself, several chapters have been devoted to background developments to the establishment of the FSAW in 1954.